Pengaruh Komunikasi Krisis Public Relations Pemerintah Kota Surakarta Terhadap Penggunaan Media Oleh Masyarakat Mengenai Pandemi Covid-19 (Universitas 17 Agustus 1945 Surabaya, 2023)
The role of the media especially social media is very important in information dissemination related to Covid-19 in the digitalization era. The role of public relations is needed to deal with crisis communication. This study aims to determine the effect of the Surakarta City Government's public relations crisis communication on the use of media by the public regarding the Covid-19 pandemic. The independent variable in this study is crisis communication and the dependent variable is media use. This study uses a quantitative approach with simple random sampling method with 30 respondents. Data processing uses SPSS 25 and uses simple regression analysis with the t test. The result of the coefficient of determination is 61.6%, which means that the public relations crisis communication variable influences the Public Media Use variable. This indicates that a good resolution of crisis communication can have a positive impact on the use of media by the public as information seekers. Keywords: Crisis communication, social media, public relations, Covid-19, Surakarta City Government